Distillation Innovative Applications and Modeling - Fernandes Mendes, Marisa (IntechOpen, 2017)
The purpose of this book is to offer innovative applications of the distillation process. The book is divided in two main sections, one containing chapters that deal with process design and calculations, and the other, chapters that discuss distillation applications. Moreover, the chapters involve wide applications as in fruit spirits production, in organic liquid compounds produced by oil and fats cracking, energy evaluation in distillation processes, and applicability of solar membrane distillation. I believe that this book will provide new ideas and possibilities of the development of innovative research lines for the readers.